A mechanistic approach to the in-vitro resistance modulating effects of fluoxetine against meticillin resistant Staphylococcus aureus strains. (February 2019) - Batista de Andrade Neto, João; Alexandre Josino, Maria Aparecida; Rocha da Silva, Cecília; de Sousa Campos, Rosana; Aires do Nascimento, Francisca Bruna S.; Sampaio, Letícia Serpa; Gurgel do Amaral Valente Sá, Lívia; de Sá Carneiro, Igor; Dias Barroso, Fátima Daiana; Juvêncio da Silva, Lisandra; Lima de Mesquita, Jacó Ricarte; Cavalcanti, Bruno Coelho; et al.
Abstract: Emergence of methicilin resistant Staphylococcus aureus (MRSA) strains is a major cause of infirmity worldwide and has limited our therapeutic options against these pathogens. In this regard, the search for candidates with an antimicrobial activity, with a greater efficacy and a lower toxicity, is necessary. As a result, there is greater need to search for resistance modifying agents which, in combination with existing drugs, will restore the efficacy of these drugs. The antibacterial effect of fluoxetine was determined by a broth microdilution method (the M07-A9 method of the Clinical and Laboratory Standard Institute) and flow cytometry techniques in which the probable mechanism of action of the compound was also assessed. The isolates used in the study belonged to the Laboratory of Bioprospecting of Antimicrobial Molecules (LABIMAN) of the Federal University of Ceará. After 24 h, Methicillin-resistant Sthaphylococcus aureus (MRSA) strains showed fluoxetine MICs equal to 64 μg/mL and 128 μg/mL, respectively. Cytometric analysis showed that treatment with fluoxetine caused alterations to the integrity of the plasma membranes and DNA damage, which led to cell death, probably by apoptosis. Highlights: Fluoxetine showed an in vitro activity against methicillin-resistant strains Sthaphylococus aureus. The fluoxetine acted as a bactericidal agent. The fluoxetine cause bacterial death after damaging the plasma membrane. The fluoxetine activates apoptotic signaling pathways and leads to dose-dependant cell viability loss.